2020
DOI: 10.3389/fagro.2020.577911
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Genotype × Environment Interaction for Identification of Stable Genotypes to Grain Yield in Mungbean

Abstract: In the present study, fifty-two mungbean (Vigna radiata) genotypes were evaluated for seven morphological traits at three different environments in South Indian state Tamil Nadu, namely Virinjipuram (E1), Eachangkottai (E2), and Bhavanisagar (E3) during Kharif 2017, 2018, and 2019, respectively. The data collected were subjected to variability and correlation analyses, followed by stability analysis using additive main effects and multiplicative interaction (AMMI) model, genotype and genotype × environment int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
7
16
0
1
Order By: Relevance
“…A vertical line to the AEC axis indicated that G36, G5, G15, G2, and G9 were stable and good-to low-yielding genotypes. Similar results were reported for cowpea [51] and mungbean [50][51][52][53]. The projection on the AEA was nearer to zero for the genotypes G18 and G29 followed by G31 and G36, indicating the limited interaction between these genotypes and environments.…”
Section: Discussionsupporting
confidence: 83%
“…A vertical line to the AEC axis indicated that G36, G5, G15, G2, and G9 were stable and good-to low-yielding genotypes. Similar results were reported for cowpea [51] and mungbean [50][51][52][53]. The projection on the AEA was nearer to zero for the genotypes G18 and G29 followed by G31 and G36, indicating the limited interaction between these genotypes and environments.…”
Section: Discussionsupporting
confidence: 83%
“…The presence of a significant proportion of GEI is necessary for stability analysis of rice. This is in harmony with the findings of Samyuktha et al, (2020) in mungbean.…”
Section: Combined Analysis Of Variancesupporting
confidence: 91%
“…В наших исследованиях в обоих пунктах изучения образцов наблюдалась сильная изменчивость фенологических и хозяйственно ценных признаков и их зависимость от условий произрастания. Зависимость урожайности маша от погодных условий и генотипа неоднократно отражена в научной литературе (Ullah et al, 2012;Win et al, 2018;Samyuktha et al, 2020). При эколого-географическом изучении маша в шести климатических зонах Индии получены сопоставимые с нашими результаты о влиянии климатических условий и генотипа на размер семян и продуктивность семян с растения (Thangavel et al, 2011).…”
Section: Discussionunclassified